Avaliação da deposição da calda de pulverização em função do tipo de ponta e do volume aplicado, na cultura do feijão - Limberger, Aline Regina (2006)
The culture of the beans (Phaseolus vulgaris L.) is one of most important in Brazilian agriculture. The occurrence of illnesses is a serious factor of influence in its development and productivity. One of the critical points of the current system of production of agricultural cultures is the use of defensive defensive, besides raising the production cost, can cause direct and indirect ambient contaminations. The choice and the adequate use of spraying beaks are essential for the correct application of defensive. Due to those needs the present work was carried out in Cascavel PR, in the harvest 2004/2005, using the beans IAPAR 81, with the objective evaluating the amount of syrup deposited on the beans leaves, varied the volume of syrup applied and the beaks types used in the spraying bar, used tracer substance, simulating the physical characteristics of the solutions of the products. To evaluate the spraying distribution, fifteen leaves were collected per plant in different extracts (higher, medium and lower), with the purpose of evaluating the syrup penetration, in agreement with the different beaks and applied volumes. The experimental design was arranged in randomized complete blocks, in factorial arrangement, with four beaks and point of the type simple fan, double fan, double fan with air injection and empty cone and 3 syrup volumes (100, 200 and 300 L ha-1). In agreement with the results obtained and in the conditions that the present work was carried out.,concluded that: The syrup volume that presented larger depositions , in different extracts of the beans plants was of 300 L ha-1; for larger depositions in the higher extract of the beans plants, the best combination is to use beaks of Empty Cone, with volumes of the 300 L ha-1 and for larger depositions for the medium and lower extracts of the bean plants, the best combination is to use peaks Double Fan with air injection, volumes of 100, 200 or 300 L ha-1